2011
DOI: 10.1063/1.3615782
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence enhancement in CdS nanoparticles by surface-plasmon resonance

Abstract: Precise control of photoluminescence enhancement and quenching of semiconductor quantum dots using localized surface plasmons in metal nanoparticles

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 31 publications
2
50
0
Order By: Relevance
“…To examine the influence of metal nanoparticles on the photoluminescence of semiconductors, colloidal mixtures of CdS and Au nanoparticles were prepared with different CdS/Au fractions. [58] The photoluminescence emission spectra of the mixed CdS/ Au nanoparticles were measured under excitation of 400 nm at room temperature ( Fig. 11(a)).…”
Section: Photoluminescence Enhancement By Surface-plasmon Resonancementioning
confidence: 99%
See 1 more Smart Citation
“…To examine the influence of metal nanoparticles on the photoluminescence of semiconductors, colloidal mixtures of CdS and Au nanoparticles were prepared with different CdS/Au fractions. [58] The photoluminescence emission spectra of the mixed CdS/ Au nanoparticles were measured under excitation of 400 nm at room temperature ( Fig. 11(a)).…”
Section: Photoluminescence Enhancement By Surface-plasmon Resonancementioning
confidence: 99%
“…[56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71] Surface-plasmon resonance induced by the oscillation of the charge density of conduction electrons, and its corresponding electromagnetic field can strongly affect the optical properties of any semiconductor nanoparticles nearby.…”
Section: Introductionmentioning
confidence: 99%
“…7. The fluorescence enhancement can be explained by interaction between OBs and GNPs [12][13][14][15]. A numerous reports have shown that the interaction between fluorophores and metal nanoparticles depending on the distance between…”
Section: Resultsmentioning
confidence: 99%
“…Obviously, the FRET follow the opposite behavior of the PL lifetime due to it mainly depend on it. [42] In addition to the cross-section values, the effectiveness of a laser oscillator or amplifier is strongly affected by the amount of resonant absorption at the extraction wavelength. In this case it is essential to estimate some spectroscopic parameters (β min , I sat and I min ) that being used for evaluating the lasing properties of the material.…”
Section: Figure (3b) Illustrates That the Energy Transfer Between Ag mentioning
confidence: 99%